2021
DOI: 10.3390/jcm10020344
|View full text |Cite
|
Sign up to set email alerts
|

Early Pregnancy Outcomes in Fresh Versus Deferred Embryo Transfer Cycles for Endometriosis-Associated Infertility: A Retrospective Cohort Study

Abstract: Given the estrogen-dependence associated with endometriosis, hyper-stimulation associated with assisted reproduction treatment may exacerbate the disease process and adversely affect endometrial receptivity and subsequent implantation. In this way, a freeze-all deferred embryo transfer (ET) approach may benefit patients with endometriosis, although controversy exists regarding the mechanism of endometriosis-associated infertility and benefits of deferred ET on endometrial receptivity. Hence, the purpose of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…They compared two matched groups of frozen embryo transfer and fresh embryo transfer in terms of implantation rate, clinical pregnancy rate and miscarriage rate. They found that there was no signi cant difference between two groups [19]. Contrary to their study our results show clinical pregnancy rate was signi cantly higher in frozen embryo transfer group, however, miscarriage rate was similar in both groups.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…They compared two matched groups of frozen embryo transfer and fresh embryo transfer in terms of implantation rate, clinical pregnancy rate and miscarriage rate. They found that there was no signi cant difference between two groups [19]. Contrary to their study our results show clinical pregnancy rate was signi cantly higher in frozen embryo transfer group, however, miscarriage rate was similar in both groups.…”
Section: Discussioncontrasting
confidence: 99%
“…In past studies, the difference in the pregnancy rate between two methods of IVF, including frozen embryo transfer and fresh non-frozen embryo transfer, has been observed in patients with endometriosis. In some studies, use of frozen embryo transfer increases the pregnancy rate [9,17,18] however, in another study it does not change the pregnancy rate [19], therefore, fertility outcomes in endometriosis patients receiving IVF needs more evaluation in terms of the type of transferred embryo. The purpose of this study is the comparison of pregnancy outcomes in two methods of IVF, including frozen and fresh embryo transfer, in infertile women with endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to autoantibody-mediated mechanisms, other immune-mediated factors that may contribute to infertility and impaired implantation in autoimmune diseases and endometriosis have been described. These factors include alterations in the balance of proinflammatory and anti-inflammatory cytokines, changes in the composition and/or activity of specific endometrial immune cells, and aberrant expression of adhesion molecules at the implantation site [39]. Recent studies have, in fact, shown that women with endometriosis present dysregulation of key endometrial receptivity-specific genes often belonging to immunological pathways [40].…”
Section: Comparison With the Existing Literaturementioning
confidence: 99%
“…76 With regards to embryo transfers, some studies suggest that in women with advanced endometriosis, frozenthawed embryo transfer (FET) seem to offer 1.5 times higher cumulative live birth rates compared to embryo transfers (ET) in a natural cycle. [77][78][79][80][81] However, a recent Cochrane review, revealed that fresh and frozen-thawed embryo transfers offer similar success rates. [82][83][84][85] Ovarian tissue cryopreservation in women with endometriosis.…”
Section: Oocyte and Embryo Cryopreservation In Patients With Endometr...mentioning
confidence: 99%